The Effect of the Marketing Mix (4Ps) and Brand Image on Customer Loyalty Through Customer Satisfaction: A Case Study of Ibis Styles Yogyakarta - Sabarihut Tua Sitompul; Myrza Rahmanita; Nurbaeti Nurbaeti; Surya Fadjar Boediman (Sahabat Publikasi, 2026)
This research aims to analyze the effect of the marketing mix (4P) and brand image on customer loyalty, with customer satisfaction as a mediating variable, among customers of Ibis Styles Yogyakarta Hotel. This research employed a quantitative approach through questionnaires distributed to 200 respondents who were customers of the hotel. The data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the assistance of SmartPLS version 3.2.7. The hypothesis testing results show that the marketing mix has a positive and significant effect on customer satisfaction (t = 4.416; p = 0.000) and on customer loyalty (t= 2.196; p = 0.028). Brand image also has a positive and significant effect on customer satisfaction (t= 5.853; p = 0.000) and on customer loyalty (t= 3.727; p = 0.000). Furthermore, customer satisfaction has a positive and significant effect on customer loyalty (t= 4.025; p = 0.000) and is proven to act as a significant mediator in the relationship between the marketing mix and customer loyalty (t= 2.968; p = 0.003), as well as between brand image and customer loyalty (t= 3.480; p = 0.001). These findings confirm that effective implementation of the marketing mix and strong brand image management can enhance customer satisfaction, which in turn drives increased customer loyalty. This study is expected to contribute academically to the development of hospitality marketing literature and to provide practical implications for the management of Ibis Styles Yogyakarta in formulating marketing strategies oriented toward customer satisfaction and loyalty.